2020
DOI: 10.1111/sms.13770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eccentric training at long‐muscle length on architectural and functional characteristics of the hamstrings

Abstract: Hamstring strain injury (HSI) is the most common non-contact muscle injury in high-speed running sports, such as soccer, track and field, rugby, American football, and Australian football, with biceps femoris long head (BFlh) being predominantly affected (for review, see Erickson and Sherry). 1 In addition, studies report a rate of 16%-23% for HSI recurrence in some of these sports, while previous HSI present the greatest risk factor for the occurrence of the HSI. 1 The majority of HSIs occur during maximal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 41 publications
(181 reference statements)
1
55
0
Order By: Relevance
“…A SRMA showed a limited to moderate confidence in evidence that eccentric training performed for a minimum of 4 weeks decreased the BFlh pennation angle ( Gérard et al, 2020 ), which was also shown in a recent study ( Marušič et al, 2020 ). However, another study with 32 soccer players (age, 18–23 years) performing an 8-week NHE program once a week versus twice a week showed no between-group differences in BFlh pennation angles ( Medeiros et al, 2020 ).…”
Section: Part 2: Anatomic and Physiologic Variations Of The Hamstrings And Potential Implications For Injury Risksupporting
confidence: 65%
See 1 more Smart Citation
“…A SRMA showed a limited to moderate confidence in evidence that eccentric training performed for a minimum of 4 weeks decreased the BFlh pennation angle ( Gérard et al, 2020 ), which was also shown in a recent study ( Marušič et al, 2020 ). However, another study with 32 soccer players (age, 18–23 years) performing an 8-week NHE program once a week versus twice a week showed no between-group differences in BFlh pennation angles ( Medeiros et al, 2020 ).…”
Section: Part 2: Anatomic and Physiologic Variations Of The Hamstrings And Potential Implications For Injury Risksupporting
confidence: 65%
“…However, another study with 32 soccer players (age, 18-23 years) performing an 8-week NHE program once a week versus twice a week showed no between-group differences in BFlh pennation angles (Medeiros et al, 2020). A prospective controlled study with soccer players analyzed the NHE and sprint interventions, showing that only the NHE induced small increases in the BFlh pennation angle (Mendiguchia et al, 2020), contradicting the decreases seen in previous studies (Gérard et al, 2020;Marušič et al, 2020). Results are conflicting, largely limited to the BFlh and involve a narrow set of exercise modalities.…”
Section: Dissectionmentioning
confidence: 84%
“…A systematic review with meta-analysis of 11 RCTs comparing strength training to stretching for ROM gains has found that for interventions lasting 5 and 16 weeks, the strength training and stretching protocols did not differ in their effects on ROM (Afonso et al, 2021b). To different degrees, eccentric and concentric strength training with full ROM, as well as plyometric training, induce changes in muscle fascicle length and pennation angle, and tendon extensibility, resulting in ROM gains (Reeves et al, 2009;Kubo et al, 2017;Valamatos et al, 2018;Gérard et al, 2020;Marušič et al, 2020). However, the studies included in the review of Afonso et al (2021b) had considerable heterogeneity in design, populations and protocols.…”
Section: "Can I" Vs "Do I Have To" Stretch To Chronically Improve Range Of Motion?mentioning
confidence: 99%
“…[80] Likewise, a recent study showed that 12 sessions of eccentric ST increased fascicle length of the biceps femoris long head. [29] However, ST with an emphasis in concentric training has been shown to increase fascicle length when full ROM was required. [28] In a study with nine older adults, ST increased fascicle length in both the eccentric and concentric groups, albeit more prominently in the former.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…[27] ST focused on concentric and eccentric contractions has been shown to increase fascicle length. [28][29][30] Better agonist-antagonist co-activation[31], reciprocal inhibition, [32] and adjusted stretch-shortening cycles [33] may also explain why ST is a suitable method for improving ROM.…”
Section: Introductionmentioning
confidence: 99%